Conversion of Triple Bonds into Single Bonds in a Domino Carbopalladation with Norbornene. Issue 23 (3rd November 2017) - Zhu, Chuanle; Chen, Pengquan; Zhu, Rui; Jiang, Guangbin; Lin, Zhiming; Wu, Wanqing; Jiang, Huanfeng
Abstract: A domino carbopalladation reaction of haloalkynes is presented. Remarkably, the four‐time carbopalladation process converts the carbon‐carbon triple bonds of haloalkynes stepwise into carbon–carbon double bonds, and finally to carbon‐carbon single bonds. Features of this reaction are that the carbon‐carbon double bonds of stable vinyl palladium intermediates are transformed into carbon‐carbon single bonds with the generation of unstable alkyl palladium intermediates. The subsequently formed π‐allylpalladium species are independently trapped by N ‐tosylhydrazones, boronic acids, and B2 pin2 in a highly diastereoselective manner, delivering the corresponding polycyclic and twisted products with a bicyclo[3.2.1]oct‐2‐en‐3‐yl)tricyclo[3.2.1.0 2, 4 ]octane core skeleton in moderate to good yields via C−C and C−B bond formations. Significantly, the dual roles of norbornenes, ring construction and ring expansion, and the identification of electron‐rich tri(2‐furyl)phosphine as the ligand are found to be critical for the success of these transformations. Abstract : Delivery with Domino's : A four‐time domino carbopalladation process is presented which converts the triple bonds of haloalkynes into single bonds. The subsequently formed π‐allylpalladium species are independently trapped by N ‐tosylhydrazones, boronic acids, and B2 pin2 in a highly diastereoselective manner via C−C and C−B bond formations.